The Role of the Family in Educating a Democratic and Civilized Generation - Hajri, Priazki; Porta, Tom; Sastra Atmaja, Thomy; Wayan Landrawan , I (Jurnal Penelitian dan Pengabdian, 2023)
The family plays a very important role in shaping the character and values of the younger generation. In the context of an increasingly plural and developing society, families have a significant responsibility to educate their children to grow into democratic and civilized individuals. Education within the family not only encompasses cognitive aspects but also moral, social, and emotional aspects that shape children’s attitudes and behaviors in daily life. This article discusses how families can play the role of the first institution to instill the values of democracy, tolerance, and ethics in national and state life. With an approach based on open communication, the formation of empathy, and the teaching of justice values, families can make a significant contribution to creating a civilized generation ready to actively participate in democratic life.